Selection of corn cultivars for yield, stability, and adaptability in the state of Amazonas, Brazil - Oliveira, Inocencio Junior; Atroch, André Luiz; Dias, Miguel Costa; Guimarães, Lauro José Moreira; Guimarães, Paulo Evaristo de Oliveira (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate corn cultivars grown in the state of Amazonas, Brazil, which simultaneously show high grain yield, adaptability, and stability. The trials were carried out in seven environments in the state of Amazonas, in a randomized complete block design, with two replicates. The grain yield of 30 corn cultivars was evaluated in four growing seasons, from 2011/2012 to 2014/2015. The genetic parameters were estimated by the REML/Blup methodology. The selection for adaptability and stability was based on the predicted genetic value and on the harmonic mean of the relative performance of the genetic values. Despite the existence of genotype x environment interaction, cultivars with high adaptability and stability were identified. Iranduba – lowland, in 2011/2012 and 2014/2015 – and Rio Preto da Eva – upland, in 2012/2013 – stood out as favorable environments, while Iranduba – upland, in 2011/2012 and 2012/2013 – and Manaus – upland, in 2012/2013 and 2013/2014 – were classified as unfavorable environments. The single-cross hybrid BRS 1055 showed productive superiority and high stability in this region. The Sint 10771, Sint 10781, and Sint 10699 synthetic varieties showed high adaptability. BRS Caimbé shows specific adaptability to cropping in upland environments of the state of Amazonas, Brazil.